2021
DOI: 10.1002/ccr3.4357
|View full text |Cite
|
Sign up to set email alerts
|

Successful determination of imatinib re‐administration dosage by therapeutic drug monitoring in a case of chronic myeloid leukemia initiating dialysis for acute renal dysfunction

Abstract: Fixed dose regimen is currently the standard administration method for TKI. However, this case report indicated that TDM may by a useful approach to individualized dosing of TKI for the treatment of CML when initiating dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We developed a rapid, sensitive, and efficient UPLC-MS/MS method to simul ously determine osimertinib, aumolertinib, and furmonertinib concentrations in hu Therapeutic drug monitoring (TDM) is an important technique for formulating dosing regimens for drugs with strong toxic effects, and great individual differences measured by drug concentrations in biological samples can identify inter-patient differences and improve the therapeutic effects of drugs while reducing AEs [22][23][24]. Several studies have also shown that TDM can improve the therapeutic efficacy of TKIs, supporting rational clinical use [25][26][27][28]. The ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method is a standard analytical tool for TDM and is widely used in clinical practice for precise treatment with targeted oral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a rapid, sensitive, and efficient UPLC-MS/MS method to simul ously determine osimertinib, aumolertinib, and furmonertinib concentrations in hu Therapeutic drug monitoring (TDM) is an important technique for formulating dosing regimens for drugs with strong toxic effects, and great individual differences measured by drug concentrations in biological samples can identify inter-patient differences and improve the therapeutic effects of drugs while reducing AEs [22][23][24]. Several studies have also shown that TDM can improve the therapeutic efficacy of TKIs, supporting rational clinical use [25][26][27][28]. The ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method is a standard analytical tool for TDM and is widely used in clinical practice for precise treatment with targeted oral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…between post-24h of Wednesday and pre-dialysis of Thursday) did not show any statistically significant difference. Probably, as hypothesized in a LMC study [ 27 ], due to hemodialysis, the steady state was not yet reached after one week from the start of treatment, as it normally happens in patients with normal renal function. Since RBC have some of the transporters used by imatinib to move through the cellular membrane [ 20 , 21 ] we also analyzed levels of imatinib in those cells, which remained relatively constant over time.…”
Section: Discussionmentioning
confidence: 99%
“…Among chronic myeloid leukemia patients, in one study a progressive increase of plasma levels of imatinib was reported, causing severe adverse effects requiring dose reduction [ 26 ]. In a more recent study, levels of imatinib were evaluated with a single analysis at day 8 and 28, with evidence of a large fluctuation of values, thought to occur because the steady state was reached on day 28 after re-administration [ 27 ]. The patient did not experience any clinically relevant toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 A few studies have reported imatinib-related renal dysfunction and haematological toxicity. 16 Measuring creatinine concentration is not a reliable test for renal function; glomerulus filtration rate (GFR) estimation is a reliable or more validated assessment tool. 17 Several pieces of evidence have recommended that imatinib 400mg/day treatment is responsible for improved survival with a high rate of clinical outcomes or responses.…”
Section: Introductionmentioning
confidence: 99%